EXPRESSION AND LOCALISATION OF ADIPONECTIN AND ITS RECEPTORS IN HUMAN OCULAR TISSUES - VIDHYA SRINIVASAN,; PALANISAMY KARTHIKKA,; KARUNAKARAN CORAL,; SUBBULAKSHMI CHIDAMBARAM,; PUKHRAJ RISHI,; KONERIRAJAPURAM NATARAJAN SULOCHANA, (International Journal of Pharma and Bio Sciences, 2014)
Recently we have reported the elevated levels of Adiponectin (APN) in proliferative diabetic retinopathy (PDR) vitreous in comparison to macular hole. It has been assumed that APN may get exudated into vitreous from circulation but no experimental proof has been shown so far. Therefore we set out to determine the origin of APN in the vitreous.Donor eye balls were used to extract RNA and protein for real time PCR, western blotting. Five micron retinal sections were done for immunofluorescence and immunohistochemistry. Primary retinal epithelial and endothelial cells were isolated from donor eye balls aged below 50 years.APN exerts its function through two receptors, AdipoR1 and AdipoR2. Interestingly we identified the expression of APN, AdipoR1 and AdipoR2 mRNA transcripts in all ocular tissues by quantitative PCR. Immunofluorescence and western blot analysis demonstrated the presence of APN and its receptors AdipoR1, AdipoR2 in all ocular tissues. AdipoR1 and AdipoR2 were distributed more in the retinal and choroidal layers as observed by immunohistochemistry. Surgically removed epiretinal membrane (ERM) showed a strong expression of mRNA transcript of APN and its receptors and immunofluorescence studies revealed the presence of protein as well. We have also confirmed the expression in primary human retinal endothelial cells (hREC), human choroidal endothelial cells (hCEC) and human retinal pigment epithelial cells (hRPE).Given the fact that APN regulates vasodilatation in retinal arterioles and inhibits choroidal neovascularization in animal models, it was unclear whether APN and it receptors exist in the human eye; our study has shown the localized expression of APN, AdipoR1 and AdipoR2 in different ocular tissues.